Isolation and characterization of Siphoviridae phage infecting extensively drug-resistant Acinetobacter baumannii and evaluation of therapeutic efficacy in vitro and in vivo. Issue 7 (6th June 2019) - Wintachai, Phitchayapak; Naknaen, Ampapan; Pomwised, Rattanaruji; Voravuthikunchai, Supayang Piyawan; Smith, Duncan R.
Abstract : Purpose . Extensively drug-resistant (XDR) strains of Acinetobacter baumannii are being reported worldwide, and they are associated with high morbidity and mortality rates. These strains are considered to be the highest priority for the development of new antibacterial agents. Therefore, we aimed to develop an effective alternative antimicrobial agent. Methodology. Bacteriophages (phages) were enriched and recovered from a hospital waste water sample after activated sludge treatment. The biological characteristics and therapeutic efficacy of the phages were evaluated in vitro and in vivo . Results . Phage AB1801 was able to infect 70 % of XDR A. baumannii isolates and showed high pH, temperature and storage stability, with rapid adsorption (>80 % adsorbed in 10 min), a short latent period (20 min) and a large burst size (212 p.f.u./cell). The phage was classified as being in the order Caudovirales, family Siphoviridae . Phage AB1801 inhibited biofilm formation and reduced preformed biofilms in a dose-dependent manner. The prophylactic and therapeutic efficacy of AB1801 towards XDR A. baumannii infection was evaluated in Galleria mellonella larvae and the phage showed significant protective effects in both prophylactic and therapeutic treatment modalities. Conclusion . These studies suggest that phage AB1801 may be suitable for further development as an antimicrobial agent against XDR A. baumannii infection.